SISTEM INFORMASI SERVICE MOBIL DI BENGKEL SUN SEMARANG - Chandra Devi, Bella; Mariana, Novita (Information Technology and Telematics, 2018)
Abstract: Sun Car Repair Shop is a business engaged in car repair services. Every day many customers come to repair cars. Every day many customers come to repair cars. But even though there are quite a lot of customers coming in, the provision of service information needed by customers is still very lacking. Customers get the service information needed if they ask directly to the workshop by telephone or the workshop itself is contacting the customer. Data recording about service is also still done by using manual recording in a normal book. From this problem, Sun's workshop requires a web-based car workshop information system. With this system, it is expected that customers can get the required data service information such as car damage, completion time, photos when repairing, service details. While the Admin can do data collection to the system and can check service history. Admin can make monthly reports for the owner. In designing this system using the PHP programming language. System development method uses the waterfall method. System design tools using DFD and ERD.